Haida totem pole from Kaigani, Prince of Wales Island, Alaska, early 20th century (1900)
This totem pole was purchased by the donor at the Ye Olde Curiosity Shop in Seattle. It was originally from the Haida tribe on Prince of Wales Island. The top two figures represent the twins of the Chief in whose honor this pole was erected. The next figure is a Medicine Man with the Frog, or sign of the evil spirits firmly in his mouth, portraying his power over these spirits. The next lower figure is the Grizzly Bear who was noted for his courage and strength. The Bear was also a friend in that, by observing the roots and herbs he ate, the native people could also select safe subsistence to eat. The face below the Bear represents the Chief holding a copper which is a sign of wealth. 1 Pole, Totem; Materials: wood --paint --metal; Dimensions: 110 in.H x 13 in.W x 16 in.D Base: 2 in.H x 21 in.W x 21 in.D